2007
DOI: 10.1007/s00259-007-0379-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging early changes in proliferation at 1 week post chemotherapy: a pilot study in breast cancer patients with 3′-deoxy-3′-[18F]fluorothymidine positron emission tomography

Abstract: [18F]FLT-PET can detect changes in breast cancer proliferation at 1 week after FEC chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
195
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(209 citation statements)
references
References 17 publications
11
195
2
1
Order By: Relevance
“…Shields et al [34] evaluated an unknown number of lesions in six patients using SUV max and SUV mean (50% threshold technique) and carried out full kinetic analyses (NLR with a b c d Results in breast cancer [15] are also consistent with the present results with reported ICCs of 0.99 and 0.97, and SDs of 11% and 15% for SUV and Patlak K i , respectively. Differences in study design and methods, however, make it difficult to perform a direct comparison.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Shields et al [34] evaluated an unknown number of lesions in six patients using SUV max and SUV mean (50% threshold technique) and carried out full kinetic analyses (NLR with a b c d Results in breast cancer [15] are also consistent with the present results with reported ICCs of 0.99 and 0.97, and SDs of 11% and 15% for SUV and Patlak K i , respectively. Differences in study design and methods, however, make it difficult to perform a direct comparison.…”
Section: Discussionsupporting
confidence: 87%
“…Unfortunately, NLR3k-derived k 3 showed poor reproducibility. However, both K i and SUV have shown good correlations with other proliferation markers, with K i having the strongest correlation [4,15,33]. The present results indicate that both K i and SUV are reproducible.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…70 Early studies on breast cancer have also demonstrated that changes in FLT uptake during treatment predict clinical response, and multicenter trials for breast cancer are ongoing. 71,72 In patients with nonsmall cell lung cancer, a reduction in FLT uptake after 7 days of therapy with gefitinib was highly predictive of tumor response on CT and of progression-free survival. 73 This is a notable result, in that proliferation imaging was effective for predicting response to a biologically targeted agent that often has a cytostatic response when used as monotherapy.…”
Section: Imaging Proliferationmentioning
confidence: 99%